ENGLISH WRITERS ON THE ARAB WORLD - Baban, Dr. Naman (مجلة كلية الاداب, 1972)
Lecturer of English Liter. University of Libya. Faculty of Arts. Many English writers have begun to tackle foreign themes after fai ring-for a variety of reasons-to find anything attractive in the home-scene that might be used as material for their literary works. This new pheno menon can clearly be seen if we look at the literary achievements in Eng land from the first quarter of the Twentieth century when almost all the works dealt exclusively with the home-scene. This was, of course a reflec tion of the existing social, political and economic conditions in England at that time, and the many lively themes and the burning issues that had been used as the source and stimulation for English literature. This period, the late Victorian, heralded the disintegration that became the dominant aspect of Britain's social, economic and political life after the period of stability and economic prosperity ushered by the Industrial Revolution. The period following the First World War was marked by a literature em bracing the revolt against the Victorian social order, against the Victorian ethics. Thus at the beginning of this century writers were deeply involved in a battle with the values of their society to pay the least attention to the values of another world beyond Britain's frontiers : « But it was also an era of desperation – of a hectic and bloody im perial race against new upstart competitors, of the first modern eco nomic slump, of the rise of the Labour movement as we know it, of 23 the dock strike and Bloody Sunday, of the impact of Darwin and T.H. Huxley, of William Morris and Bernand Shaw.... (1) And during the period of the 1930's and the years before and after the Second World War English literature went through a crisis that left its marks on the attitudes to life of writers, on their social and economic sta tus, and on the form and content of their literary works. This period ma nifested deeper changes than any other transition period in previous his torical changes in Britain. The present transition period has produced more deeply-felt effects in the ranks of writers because it demanded from them a clearer vision of the new period : «In former transitions the elements of similarity between the old and the new cushioned the shocks of change; but now there seems to be no comfortable continuity.» (2) This transition period has sown the seeds of crisis in the cultural life of Britain, affecting all aspects of its creative process. Thus the new values of life in Britain, with all the complications of economic growth, began to demand from the writer an explanation of the new changes, an act that implies on the part of the writer a solid vision of the future. The imapct of this demand on the writers had evidently increased in the period of the Second World War as the British people began to assert the necessity of explaining their world through literature. The response to this demand varied from one writer to another. In addition, the spiritual condition of post-war Britain was clouded with gloomy signs threatening the status of the writer whose exsitence in this society brought him face to face with almost insoluble problems: «As for professional full-time writers, 'there seems no doubt that their number is decreasing rapidly', while as for persons who write only in their spare time, they 'are losing their freedom to write as and how they wish, which the security of a job apart from writing gave them'.>(3) (1)–Kettle, Arnold : An Introduction to the English Novel. Huschin son's University Library, London 1953, Vol. II, pp. 9-10. (2)—Lindsay, Jack : After the' Thirties, The Novel in Britain and its Fu ture, Lawrence & Wishart, Lonodon 1956, P. 12. (3) Ibid., P. 70. 24